Graph Convergence and Iterative Approximation of Solution of a Set-Valued Variational Inclusions - Faizan Ahmad Khan; Sanjeev Gupta (Journal of Mathematics)
In this article, first, we introduce a class of proximal-point mapping associated with generalized αiβj-Hp.,.,…-accretive mapping. Further, we discuss the graph convergence of generalized αiβj-Hp.,.,…-accretive mapping. As an application, we consider a set-valued variational inclusion problem (SVIP) in real Banach spaces. Furthermore, we propose an iterative scheme involving the above class of proximal-point mapping to find a solution of SVIP and discuss its convergence under some convenient assumptions. An example is constructed and demonstrated few graphics in support of our main results.